PROCESSES AND PHENOMENA IN THE MICRODYNAMIC ZONES OF COVERING DEPOSITS WITHIN THE PLAIN TERRITORIES - Bublyas, V.; Bublyas, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper presents the new data on increased activity of the most of processes occurring in the microdynamic zones as compared to background areas. First of all it concerns the geomagnetic field, electromagnetic and electric fields, specific activity of radioactive gases (Rn222-220), geochemical processes, motion of pore fluids.